Group counseling training with a REBT approach for guidance and counseling teachers at the MTs in Magelang Regency - Taufik Agung Pranowo; Arip Febrianto (Universitas Muhammadiyah Magelang, 2023)
Improving the competency of guidance and counseling teachers includes both a demand and an obligation in the delivery of guidance and counseling services. The aim of this program intends to strengthen guidance and counseling teachers' competency, particularly in group counseling services. The Guidance and Counseling Teacher Consultation (MGBK) MTs Magelang Regency are the target audience for this program. This program employs lectures, group counseling practice support using the REBT technique, and activity evaluation. As the result of this program, guidance and counseling teachers at Magelang Regency MGBK MTs learned to grasp the application of group counseling using the REBT approach.